2019
DOI: 10.1101/2019.12.22.884940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual self-motion cues are impaired in Parkinson’s disease yet over-weighted during visual-vestibular integration

Abstract: Background: Parkinson's disease (PD) is prototypically a movement disorder.Although perceptual and motor functions are interdependent, much less is known about perceptual dysfunction in PD. Perceptual deficits can impact activities of daily living, and contribute to motor symptoms, but might go unnoticed if not tested directly. Posture, gait and balance, affected in PD, rely on veridical perception of one's own motion in space. Yet it is unknown whether self-motion perception is impaired in PD. Objectives:To t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 88 publications
(103 reference statements)
1
2
1
Order By: Relevance
“…Since responses are categorical (two‐alternative forced choice) and not graded motor responses, the resulting psychometric performance better isolates perceptual function. Recently, our group and another group, both tested vestibular heading discrimination in PD using this same method, but finding opposite results—Beylergil, Ozinga, Walker, McIntyre, and Shaikh (2019) found increased vestibular thresholds in PD, while we found no vestibular impairment (Yakubovich et al, in press). Our cohort were relatively early‐stage PD, while the other cohort were more advanced (with deep brain stimulation).…”
Section: Vestibular Function In Pdcontrasting
confidence: 58%
See 3 more Smart Citations
“…Since responses are categorical (two‐alternative forced choice) and not graded motor responses, the resulting psychometric performance better isolates perceptual function. Recently, our group and another group, both tested vestibular heading discrimination in PD using this same method, but finding opposite results—Beylergil, Ozinga, Walker, McIntyre, and Shaikh (2019) found increased vestibular thresholds in PD, while we found no vestibular impairment (Yakubovich et al, in press). Our cohort were relatively early‐stage PD, while the other cohort were more advanced (with deep brain stimulation).…”
Section: Vestibular Function In Pdcontrasting
confidence: 58%
“…Yet, to conclude this, an experiment that measures unisensory reliabilities and multisensory integration weights within the Bayesian framework is required (taking care that measurements of unisensory function are indeed representative, otherwise predictions may be off, Shalom & Zaidel, 2018). In our recent study of heading discrimination (Yakubovich et al, in press), we indeed found visual overweighting in PD when comparing their measured visual and vestibular integration weights to the Bayesian predictions. Thus, patients with PD may have a specific (and perhaps unique) multisensory integration impairment.…”
Section: Multisensory Integrationsupporting
confidence: 55%
See 2 more Smart Citations